Root Cause Analysis of Electrical Faults in Industry & other Facility - Md Shameem Ahsan; Md Khaledur Rahman; Manam Ahmed; Faysal Amin Tanvir; Md Saiful Islam (Journal of Renewable Energy, Electrical, and Computer Engineering, 2024)
The sole purpose of this analysis was to discuss the broader picture of fire incidents that occurred in industry due to electrical faults. Nowadays, fire incidents in industries as well as in residential and commercial buildings are a common case. Local and international print & electronic media report fire incidents every day. The fatalities are remarkable and also caused extensive property damage, and undoubtedly, it can be mitigated upon consideration of a few factors. This article identifies the exact causes of electrical faults, investigating previous fire incident reports in various industries and other possible reasons. During the past decades, there has been a noticeable change in infrastructure and industrial development worldwide. Because of land shortage and improper planning, the number of high-rise buildings in the industry sector increases without maintaining electrical standards, increasing fire incidents, fatality rates, and substantial property damages. Though strong laws, national and international standards, and regulatory measures existed, accidents occurred regularly. Also, there is no significant guideline for electrical product quality, run time, and materials selection, which plays a major role in fire incidents. This report anticipates understanding the lack in the existing system, considerable findings for installations, and extending to further studies to find out proper remediation.